2022
DOI: 10.3389/fenvs.2021.805405
|View full text |Cite
|
Sign up to set email alerts
|

Using Leaf Ecological Stoichiometry to Direct the Management of Ligularia virgaurea on the Northeast Qinghai-Tibetan Plateau

Abstract: Leaf ecological stoichiometry not only reflects the plasticity and adaptability, but also the growth of plants within environments where temperature, precipitation, and soil properties vary across an elevation gradient. Ligularia virgaurea (Maxim.) Mattf. ex Rehder & Kobuski — an invasive poisonous plant — is common in the northeast portion of China’s Qinghai-Tibetan Plateau and its presence greatly affects the native ecosystem. Based on L. virgaurea leaf carbon ([C]leaf), nitrogen ([N]leaf) and phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…Therefore, [C] leaf /[N] leaf of P. anserina decreased at higher elevations to benefit growth priority. The [N] leaf /[P] leaf of P. anserina increased with elevation, similar to the study of Cao et al (2020) on Oxytropis ochrocephala and the study of Wang et al (2019) on Sabina przewalskii in the Qilian Mountains, while Su et al (2022) found no significant changes in Ligularia virgaurea's [N] leaf /[P] leaf across elevation in the Qilian Mountains. The increasing [N] leaf /[P] leaf of P. anserina with elevation indicates that the growth of P. anserina in the study area may be more susceptible to P-limitation at higher elevations.…”
Section: Discussion E Ects Of Elevation On Leaf Ecological Stoichiome...supporting
confidence: 87%
See 3 more Smart Citations
“…Therefore, [C] leaf /[N] leaf of P. anserina decreased at higher elevations to benefit growth priority. The [N] leaf /[P] leaf of P. anserina increased with elevation, similar to the study of Cao et al (2020) on Oxytropis ochrocephala and the study of Wang et al (2019) on Sabina przewalskii in the Qilian Mountains, while Su et al (2022) found no significant changes in Ligularia virgaurea's [N] leaf /[P] leaf across elevation in the Qilian Mountains. The increasing [N] leaf /[P] leaf of P. anserina with elevation indicates that the growth of P. anserina in the study area may be more susceptible to P-limitation at higher elevations.…”
Section: Discussion E Ects Of Elevation On Leaf Ecological Stoichiome...supporting
confidence: 87%
“…Soil pH exerted a positive influence on [C] leaf , consistent with the study of Liu M. et al ( 2021 ). However, most previous studies showed that higher soil pH had a significant negative impact on [C] leaf as it inhibits photosynthesis (e.g., He et al, 2016 ; Gong et al, 2018 ; Lin et al, 2022 ; Su et al, 2022 ). These results indicated that the impact of soil pH on [C] leaf was significant but varied with species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The crushed and sieved (0.2 mm) dried samples were digested via the H 2 SO 4 -H 2 O 2 method in a digesting block at 350 °C [ 47 ] before total N and total P measurements. The total concentration of nitrogen (TN) in the plants was measured by the indophenol blue colorimetry method and assayed at 625 nm; similarly, the total concentration of phosphorus (TP) in plants was measured by the vanadium molybdate yellow colorimetric method at 450 nm [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%